[local and state labor leaders on the indoor air quality IAQ and tax issues] - Savarese, Jim (Tufts Archival Research Center, 2007)
Memo to Martin Gleason and Susan Stuntz regarding meetings in Sacramento. States the topics broached in the meeting such as indoor air quality and taxes. Claims that the trip was a huge success and that there is a lot of support for the initiation of a program in California.